Kekuatan Normatif Diplomasi Lingkungan Uni Eropa Dalam Conference of the Parties (COP) 26 - Gultom, Yosua Saut Marulitua; Manurung, Steven Montesquieu; Hutauruk, Muhammad David Ferdian; Wijaya, Muhammad Farid Gibran; Augustin, Aliffa (Hasanuddin Journal of International Affairs, 2024)
In 1992, the United Nations convened the world's largest and most important climate- related conference, the Earth Summit in Rio de Janeiro, Brazil. During the event, the United Nations Framework Convention on Climate Change (UNFCCC) was adopted. Through the UNFCCC, countries agree to stabilize greenhouse gas concentrations in the atmosphere to prevent harmful interference from human activities in the climate system. The treaty now has 197 signatures. Since 1994, the United Nations has brought together almost every country in the world to attend the World Climate Summit (Conference of the Parties (COP)) which is usually held every year. This scientific article raises the commitment of the European Union (EU) in implementing COP 26 through environmental diplomacy analysis. This scientific article aims to identify and analyze the European Union's commitment to cooperation in COP 26 in dealing with all environmental problems. Scientific articles use qualitative research methods based on literature studies. The result of this scientific article is that the European Union conducts environmental diplomacy through COP 26 by carrying out the discussions in COP 26. The conclusion of this scientific article is that COP 26 has several objectives that must be carried out by the countries involved, including the EU.     Pada tahun 1992, PBB menyelenggarakan konferensi terkait iklim terbesar dan terpenting di dunia ialah KTT Bumi di Rio de Janeiro, Brasil. Selama acara tersebut, Konvensi Kerangka Kerja PBB tentang Perubahan Iklim (United Nations Framework Convention on Climate Change (UNFCCC)) diadopsi. Melalui UNFCCC, negara-negara sepakat untuk menstabilkan konsentrasi gas rumah kaca di atmosfer untuk mencegah gangguan berbahaya dari aktivitas manusia di dalam sistem iklim. Perjanjian itu sekarang memiliki 197 tanda tangan. Sejak tahun 1994, PBB mempertemukan hampir setiap negara di dunia untuk menghadiri KTT Iklim Dunia (Conference of the Parties (COP)) yang biasa dilakukan di setiap tahunnya. Artikel ilmiah ini mengangkat komitmen Uni Eropa (UE) dalam melaksanakan COP 26 melalui analisis diplomasi lingkungan. Artikel ilmiah ini bertujuan untuk mengidentifikasi dan menganalisis komitmen kerjasama Uni Eropa di dalam COP 26 di dalam penanganan perubahan iklim. Artikel ilmiah memakai metode penelitian kualitatif berdasarkan studi literatur. Hasil dari artikel ilmiah ini ialah Uni Eropa mengadakan diplomasi lingkungan melalui COP 26 dengan menjalankan bahasan-bahasan di dalam COP 26. Kesimpulan dari artikel ilmiah ini ialah COP 26 memiliki beberapa tujuan yang harus dilaksanakan oleh negara-negara yang terlibat, termasuk UE.